KARAKTERISKTIK SIFAT FISIKO KIMIA BISKUIT TEPUNG DAUN KELOR (Moringa oleifera) DAN TEPUNG PISANG GOROHO (Musa acuminafe,sp) - Nancy Kiay; Sofyan Abdullah; Gita Suryanita Ayuba; Fadhil Abdullah (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2022)
Biscuits are a type of food made from wheat flour with the addition of other food ingredients, with a heating and printing process. The purpose of this research is to determine the influence of the comparison of Moringa leaf flour with goroho banana flour on the characteristics of biscuits, To be able to determine the ratio of Moringa leaf flour to flour the most appropriate goroho banana to produce the best quality biscuits. And to find out the results of organoleptic tests of color, scent, taste, and texture on biscuits with the addition of Moringa leaf flour as a source of antioxidants and goroho banana flour as a source of vitamins and carbohydrates. This research uses a completely randomized design (CRD) factors from this research as follows: A1 = Moringa leaf flour 20g: goroho banana flour 50g, A2 = Moringa leaf flour 30g: goroho banana flour 30g, A3 = Moringa leaf flour 50g: goroho banana flour 20g. The results of the research can be concluded that the organoleptic test is the most preferred by the panelists Color A1 with a yield of 5.08%, Aroma A1 with a yield of 5.48%, Taste A1 with a yield of 5.6%, Texture A1 with a yield of 4.92% with treatment ( Moringa leaf flour 20g: goroho banana flour 50g) and for good water content in treatment A3 with a yield of 3.44% (moringa leaf flour 50g: goroho banana flour 20g), fat content with a yield of A2 with a yield of 22% (moringa leaf flour). 30g: goroho banana flour 30g) and A1 Carbohydrate content with a yield of 4.86% (moringa leaf flour 20g: goroho banana flour 50g). So the addition of Moringa leaf flour and goroho banana flour in the manufacture of biscuits is very influential on the organoleptic test and the parameter test.